The Relationship Between Low Vitamin D Levels and the Development of Autoimmune Endocrine Diseases - Kuzio, Agnieszka; Cieplińska , Aleksandra; Ziojła-Lisowska, Kinga; Jama, Grzegorz (Quality in Sport, 2024)
Vitamin D is an essential nutrient that plays an important role in promoting overall health and well-being. Deficiencies of nutrients such as vitamin D are common in patients with autoimmune diseases. The incidence of these conditions is constantly increasing. As a result, patients are exposed to severe symptoms and discomfort in daily functioning. The causes, as well as the symptoms and complications they cause, are diverse, making diagnosis and treatment difficult. Therefore, during the clinical care of patients with AID, possible micronutrient deficiencies should be taken into account and, if observed, they should be treated with controlled supplementation. The aim of this article was to review the literature on the impact of low vitamin D status on the development of autoimmune diseases in the field of endocrinology.